AN INVESTIGATION OF TOURISM MOTIVATION AND TOURIST ATTRACTION OF TOURISTS TO BALI - Christimulia Purnama Trimurti; I Gusti Bagus Rai Utama (Jurnal Manajemen dan Kewirausahaan, 2019)
The purpose of this study was to investigate the motivation of tourists to travel to Bali. This study used a sample with 213 respondents. The analytical tool used is factor analysis with SPSS version 24. The results of the study found two tourism motivation for tourists to vacation in Bali, namely by 'Traveling & Relax' and 'Health'. We also found the results of research on the tourist attraction of tourists on vacation in Bali, namely 'Government and Private Sector', 'Public Service', 'Bali nature and culture' and 'holiday and shopping'. This study has limitations, namely not looking for a relationship between push and pull motivation of tourists to Bali.